Key ost-crisis challenges and lessons for EU energy policy - Frédéric Gonand; Pedro Linares; Andreas Löschel; David M. G. Newbery; Karen Pittel; Julio Saavedra; Georg Zachmann (EconPol Forum, 2024)
Only by decarbonizing its economy and reducing energy and raw-material dependencies can the EU safeguard its competitiveness in the global markets. Postponing policies to decarbonize the energy system will increase long-run welfare losses. Decarbonization offers great potential for improving energy security, if pursued systematically. EU energy policy must be better coordinated and provide long-run price signals. To strengthen resilience, systematic risk assessments and improved data infrastructure are essential.
Keywords: 330